Emerging New Farming Practices and their Impact on the Management of Woodlots in A1 Resettlement Areas of Mashonaland Central Province in Zimbabwe - Njaya, Tavonga; Mazuru, Nelson (Asian Development Policy Review, 2014)
The study reflected on the impact of new farming methods on the management of woodlots in A1 resettlement areas in Mashonaland Central Province in Zimbabwe. Data for the study were collected through in-depth interviews, direct observations and documentary review so as to triangulate the evidence. A structured household questionnaire was used to collect socio-economic and production data pertaining to A1 farms. The study revealed that the use of wood fuel in tobacco curing has contributed to the destruction of woodlots. Meanwhile, there is a gradual breakdown of local systems for natural resource management and the dearth of any emerging alternative institutions. The study recommended the integration of positive elements of traditional institutional set up of local communities to ensure sustainable use of natural resources and continued livelihood streams. The government should provide and empower A1 farmers with expertise on extension methods that focus on conservation and agricultural technologies that are environmentally friendly.